Chronic kidney disease in Australian Human Immunodeficiency Virus‐infected patients: Analysis of the Australian HIV Observational Database. Issue 8 (29th July 2018) - Cheung, Jason; Puhr, Rainer; Petoumenos, Kathy; Cooper, David A; Woolley, Ian; Gunathilake, Manoji; Raymond, Nigel; Varma, Rick; O'Connor, Catherine C; Gracey, David M
Abstract: Aim: The aim of the present study was to examine data from the Australian HIV Observational Database (AHOD), and firstly, to describe the incidence of chronic kidney disease (CKD) and the rate of loss of renal function in HIV‐infected individuals living in Australia, and then to examine the risk factors contributing to CKD in this population. Methods: AHOD patients over 18 years of age were eligible if they had at least two serum creatinine measurements from 1 April 2008 until 31 March 2016 and an initial estimated glomerular filtration rate (eGFR) greater than 60 mL/min per 1.73 m 3 . Cox proportional hazards models were used to assess risk factors for CKD, which included key patient demographic data and antiretroviral therapy (ART) exposure. Results: Of 1924 patients included in the analysis between April 2008 and March 2016, 81 (4.2%) developed CKD (confirmed eGFR of less than 60 mL/min per 1.73 m 3 through two consecutive eGFR measurements at least 3 months apart). Of the examined risk factors, baseline age, baseline eGFR, and the route of HIV acquisition were statistically significant predictors of development of CKD. ART exposure, viral hepatitis co‐infection, high viral load and low CD4 lymphocyte count were not found to be significant risk factors for CKD. Conclusion: This is the first study to investigate the risk factors for development of CKD among Australian HIV‐infected patients using cohort data. It highlights the need for awareness of renal risk factors, particularly among older patients or in those with pre‐existing renal dysfunction. Further research is required to explore the discrepancy between patients who have acquired HIV through different means of exposure. Summary at a Glance: This paper describes the incidence of CKD and rate of progression of CKD in a large Australian population with HIV using the Australian HIV Observational Database.